Exploring the alignment of first-year summative assessments with Bloom’s Taxonomy: A longitudinal study - dos Reis, K.; Swanepoel, C.; Yu, D.; Anciano, F. (South African Journal of Higher Education, 2022)
The correlation between the level of difficulty of assessments, Bloom’s Taxonomy as well as pass rates of courses has been a seriously under-researched area in South Africa. In this study, we proposed the revised Bloom’s taxonomy level of difficulty index, before we examined 112 first-year 2017‒2019 final and supplementary assessment papers from the Economic and Management Sciences Faculty of a university in Western Cape. The descriptive statistics showed that these assessment papers are different in terms of duration, total marks, type of questions asked as well as pass rates. It was also found that these first-year summative assessments asked questions mainly at levels two (understand) and three (apply) of the revised Bloom’s Taxonomy. In addition, the correlation and econometric analysis did not find a strong correlation between the level of difficulty index and pass rates. Nonetheless, the above-mentioned results need to be interpreted with great caution, because strictly speaking, one should also control for differences in other characteristics (e.g., students’ personal characteristics, school characteristics and lecture attendance). To conclude, there is no explicit national policy that guides higher education institutions (HEIs) on how to use Bloom’s or any other taxonomy to assess students at the appropriate National Qualifications Framework (NQF) level. Hence, our findings suggest that there is a need for a national assessment policy framework to guide HEIs on how to assess undergraduate students at different cognitive levels as required by the NQF.